HARMONI: first light spectroscopy for the ELT: final design and assembly plan of the spectrographs - Ozer, Z; Schnetler, H; Bagci, FT; Booth, M; Brock, M; Cann, N; Capone, J; Ortiz, JC; Dalton, G; Dobson, N; Foster, T; Valadez, AH; et al. (Society of Photo-optical Instrumentation Engineers, 2020)
HARMONI is the first light visible and near-IR integral field spectrograph for the ELT. It covers a large spectral range from 450nm to 2450nm with resolving powers from R (≡λ/Δλ) 3500 to 18000 and spatial sampling from 60mas to 4mas. It can operate in two Adaptive Optics modes - SCAO (including a High Contrast capability) and LTAO - or with NOAO. The project is preparing for Final Design Reviews. The instrument uses a field splitter and image slicer to divide the field into 4 sub-units, each providing an input slit to one of four nearly identical spectrographs. This proceeding presents the final opto- mechanical design and the AIV plan of the spectrograph units.